Does god speak miskitu?: Religious identity and religious nationalism among the miskitu indians of Nicaragua - Hawley, Susan (Nicaragua, 1997)
Trata Religious identity and religious nationalism among the miskitu indians of Nicaragua.
incluye índice
Keywords: 1. RESISTENCE AND IDENTITY 2. THE MISSIONFIELD